Book of days A miscellany of popular antiquities - Chambers, R. (W.R. Chambers, Ltd. London)
Over time the different seasons, months and days have acquired a particular significance, or been linked with certain historical events. Taking you through the year season by season, month by month, and day by day the "Chambers Book of Days" explores these associations.
Keywords: Popular culture -- Miscellanea; Calendar -- Miscellanea; Folklore -- Miscellanea